Turning tradition into an instrument of research: The editorship of William Nicholson (1753–1815). (17th May 2020) - Gielas, Anna
Abstract: Mainly known for its links to the periodical market and radical politics, this article recontextualizes the editorship of William Nicholson (1753–1815) in terms of its roots in the metropolitan natural philosophical circles of the second half of the 18th century as well as its impact on experimenters and men of science after 1797. The article argues that Nicholson's editorship of the Journal of Natural Philosophy, Chemistry, and the Arts was a means to expand his philosophical significance among natural philosophers at home and abroad—and was, in fact, a form of epistemological subversion that challenged the "Banksian Learned Empire."